Ukuran Pertama Kali Matang Gonad Udang Penaeus Merguiensis De Man (1988) Di Laut Arafura Pada Distrik Semangga Kabupaten Merauke - Edy H.P. Melmambessy (Universitas Musamus, Merauke, Papua, 2015)
This study aims to analyze the size of the gonads mature was the first Penaeus merguiensis shrimp in the District of Naukenjerai Merauke Regency. While its use is as an ingredient of scientific information for the benefit of the sustainable management of the shrimp. The method used is the method of survey, the location of the research: District Semangga Merauke Regency. The study was carried out between March and may of 2011. Analysis of the data are: the development of the gonads, the size of the gonads mature first, and the structure of the length of the carapace. The results obtained are (1) the size of the gonads mature first in the waters of the shrimp Penaeus merguiensis Semangga District, in the range of 51,92mm carapace length for males and 37,28 mm - 39,99 mm for females. For weight, Penaeus merguiensis shrimp reach the size of the first mature gonads in the range of 34,78 gr for males and 20,17gr for females. (2) the size of the shrimp caught is dominated by the size of the immature gonads, which is shrimp with carapace length of 26.5 mm. For the shrimp Penaeus merguiensis fishery management in waters of the Arafura Sea on Naukenjerai District, then the effort required setting nets size from 10 mm to 25.40 mm and the socialization of the regulation and supervision in the field.